Unproductive and Unfruitful Expenditure on Five Healthcare Facilities in Jharkhand - CAG of India (CAG of India)
Failure of the Departments to provide funds, create posts, purchase equipment and ensure monitoring of the works led to unproductive and unfruitful expenditure of INR 11.30 crore on five incomplete and nonfunctional healthcare facilities.